Product and process validation for cold chain free, live attenuated cholera vaccine - Chan Yean, Yean (Universiti Sains Malaysia, 2018)
A Fed- batch fermentauon prc.cess was standardized for high cell density culu~ation of th~ al!onuated choltJra Vaccinc candidate (VCUSM14P). The f£:d·batch operation resulted In the highest cell densuy of 1.81) g cells ill. The concentrated bionta!.s was used to formulate 480 vials of l•quid attenuated ~aCC'ne containing (6 x 10A8 CFU I ml). The storage stability of the vaccine formulation was evilluatdd for 1ts punty. potency and v1ab1hly by phenotypic and genotyPI•: mo;thO':ls over an el(!ended storage period of 140 days al25'C i 2 ·c and 60% 15% rela!Jve humidity on the BonctPr ICH compliant Stab•hty Chamber The viability of lhe vaccme strain (VCUSM14Pj m the fomwlat1on after 140 days of storage was recorded Cilh 6 x 10'6 CFU iml which iS 2tog~ iowei as compared to its storage at room temperature (25 • C :t 2"Cj •e; 6 x 10·'8 CFU lml and the reouct1on of CFUs might be allrobuted to the hogh humid.ty To ascerta·n the genet;c punty of VCUSM14P culture 1n the formulation. the PCR was conducted by usmg lwo dtfferent pnmer sets. The results indicate that the VCUSM14P strain~~ •nlact and comparable to the positive control VCUSM14P (unformulated) Thn vacicie cut·ure purity was validated by series of b•ochc>mical tests that are specific for Vibno cholera e. S1nce colomzalion IS critical for eliCitation of the immune response. the VCUSM i4P formulation was examined for thei coloniza!JO!lln I he 1nfant mouse model. The colonization ablhty of formulated VCUSM14 shall\ wa& good and recordod with two logs h1gher than thai of onfonnulated VCUSM14P stram ll eftec!lvely colonized and Induced a higher titer of antibodies. In order to assess whelher the vaccine fonmlla!lon Is caus•nn reactoqen•u•y, stud•es wr>re perfomtt>d "' hg;ue..i ~e.11 hlops of unvar:cm<>t<'!o rat>llil> anrt ,JnillyZP.d for the flUid accumulauon 1n cum;>.mson with ·:.old tyJ.oe and untormul;;ted VCUSM1.1P lt•e vacc•··n formulat•on was found to be non-react09enoc nt dos•J, o' 11)'5·10'6 in rabbi! Ileal loop model. The protectM! eff1cacy of vacane formulatiOn WilS delermtned by challeng•J19 .mml.ln•zed ri>hbits b)' the RevPrs•t>te lnlesllna• Tte ArJull Rabb•t Diarrhoea (RITARD) model. Rabt•rts ··acc1nat~ c~•th v<J•Xi!'10 fonnl•lallon C>l' untorl'lul<oted VCUSM :4P s•Jrvlved the chall~nge and sho;·.oJ no ~•gns or charrhoe<o and other symptoms of disease or death up lo 5 days of tha observatiOn period. Wher«>as. 100% n10rtal•ly v.as obse•ved In un,•accinated (control! r<lbb•ts ·Mfhln 18 hours post challenge l'.ilh wild lype. In conclusion. our results validate the cold chain free formulatJon of VC.:USM11P IS non-re<Jctogcn•c and •mmunogemc in vivo. and protects animals from lethal V. choleran 01~19 challenge. A Palen! for "A monovalent vaccme formula~on and a meihorl for preparai!Onlhereor was filifJd on 09/01;2018. Reference. Palen! Applicallon No Pl2018700106 at Intellectual Property Corporabon of Malaysia tMyiPO